New homogenised axial diffusion coefficients from lattice calculations. (March 2020) - Ray, Sherly; Degweker, S.B.; Kannan, Umasankari
Highlights: A new method to obtain the homogenised axial diffusion coefficient is described. The method is extended to the case of linearly anisotropic scattering. The core k-effective obtained using these diffusion coefficients is better than that by standard methods. Abstract: Expressions are derived for the homogenised axial diffusion coefficients (for isotropic and anisotropic scattering) in terms of the flux distribution available from a two-dimensional lattice calculation and collision probability like quantities that can be calculated using the numerical integration schemes employed in lattice codes for calculation of collision probabilities. An interesting observation is that the method does not require anisotropic scattering treatment in the lattice calculation for this purpose. Diffusion coefficients obtained this way (particularly in the thermal region) are significantly different from those obtained by other standard methods. Moreover, the core K-effective obtained using these diffusion coefficients agrees better with heterogeneous Monte Carlo calculations than what is obtained using other standard diffusion coefficients.